Picking the Survivor! CRISPR Reveals HIV Dependency Factors. Issue 4 (April 2017) - Schott, Kerstin; König, Renate
Abstract : A new study employs genome-wide loss-of-function CRISPR/Cas9 screening to identify three novel factors for HIV-1 entry. The factors represent promising targets for therapeutics as they are essential for HIV-1 infection, but dispensable for cell survival. The involved pathways were validated in primary CD4 + T cells, target cells for HIV-1.